2008
DOI: 10.1007/s10704-008-9265-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometric nonlinearities on damage propagation in patched beam-plates subjected to pressure loading

Abstract: The problem of edge debonding of patched beam-plates subjected to transverse pressure is examined using two related mathematical models; one which incorporates geometric nonlinearities and the other which neglects them. The models, developed in a prior study, present the energy release rates in self-consistent functional form and yield closed form analytical solutions for the specific problem of interest. Results of numerical simulations based on each model are presented in the form of debond growth paths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It was shown in [Carabetta and Bottega 2008], however, that retention of geometric nonlinearities is essential to adequately model debonding phenomena in thin structures for configurations in which the membrane force does not vanish identically. This is so regardless of whether or not buckling is an issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in [Carabetta and Bottega 2008], however, that retention of geometric nonlinearities is essential to adequately model debonding phenomena in thin structures for configurations in which the membrane force does not vanish identically. This is so regardless of whether or not buckling is an issue.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that this type of buckling is inherent to many types of composite structures and occurs due to competing mechanical and thermal elements of the loading. Most recently, Carabetta and Bottega [2008] studied the effects of geometric nonlinearities on the debonding of patched beam-plates subjected to transverse pressure. Analyses using both nonlinear and linearized models were conducted and compared.…”
Section: Introductionmentioning
confidence: 99%
“…[4] further to explore the effects of edge contact [7,8]. It was demonstrated by Carabetta and Bottega [9] that geometric nonlinearities should be retained in the analytical model to more accurately capture edge debonding behavior of such structures, echoing the sentiments of prior studies [10]. The effect of a uniform temperature difference on the debonding behavior of patched structures (when simultaneously subjected to transverse pressure) was examined by Carabetta [11], where the presence of a temperature field was shown to impact the debonding threshold.…”
Section: Introductionmentioning
confidence: 99%